Strategy Development to Improve Customer Experience Based on Customer Journey (Study on Self-Photos in Inside Studio) - Ni Luh Kadek Tri Sasi Kirani Setiawati Hartawan; Dhiyan Septa Wihara (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze Customer Experience based on the Customer Journey in photography services at Inside Studio and to identify pain points that emerge at each stage of the service process. This research employed a qualitative method with a descriptive approach through interviews with customers, staff, and the manager of Inside Studio. The findings indicate that customer experience is formed throughout all stages of the customer journey, namely before, during, and after the service, involving various touchpoints between customers and service providers. Customer experience is influenced by several key factors, including service communication quality, staff interaction, emotional experience, and operational performance. Although customers generally perceived the service experience as enjoyable and satisfying, several pain points were identified, such as slow administrative responses, inconsistent information, lack of staff proactiveness, limited facilities, and internal miscommunication. Therefore, an integrated service development strategy between front-stage and back-stage services is needed through improving communication, interaction quality, operational management, and experience-based service innovation in order to create a more optimal customer experience.